2019
DOI: 10.1021/acs.jpcb.9b08197
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Speciation and Electrochemistry of Uranyl Ions in Deep Eutectic Solvents

Abstract: Understanding the speciation of metal ions in heterogeneous hydrogen-bonded deep eutectic solvents (DES) has immense importance for their wide range of applications in green technology, environmental remediation, and nuclear industry. Unfortunately, the fundamental nature of the interaction between DES and actinide ions is almost completely unknown. In the present work, we outline the speciation, solvation mechanism, and redox chemistry of uranyl ion (UO2 2+) in DES consisting of choline chloride (ChCl) and ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 65 publications
0
26
0
Order By: Relevance
“…Abbott et al. , reported that Maline has a higher solvation potential for hardly soluble metal oxides than the reline and ethaline. Gupta et al have described the dissolution of uranyl nitrate and uranium oxides with higher stoichiometric DESs urea/ChCl (2:1) (reline) and PTSA/ChCl (1:2), respectively . Moreover, the dissolution of other uranium matrices such as Rb 2 (U­(SO 4 ) 3 ), uranium metal powder, U 3 Si 2 , (U, Pu)­O 2 , and PuO 2 has not been explored in their studies. , Previous literature reports , imply that the urea (reline) and para-toluene sulphonic acid (PTSA) act as monodentate ligands via the oxygen atom.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Abbott et al. , reported that Maline has a higher solvation potential for hardly soluble metal oxides than the reline and ethaline. Gupta et al have described the dissolution of uranyl nitrate and uranium oxides with higher stoichiometric DESs urea/ChCl (2:1) (reline) and PTSA/ChCl (1:2), respectively . Moreover, the dissolution of other uranium matrices such as Rb 2 (U­(SO 4 ) 3 ), uranium metal powder, U 3 Si 2 , (U, Pu)­O 2 , and PuO 2 has not been explored in their studies. , Previous literature reports , imply that the urea (reline) and para-toluene sulphonic acid (PTSA) act as monodentate ligands via the oxygen atom.…”
Section: Resultsmentioning
confidence: 99%
“…Gupta et al have described the dissolution of uranyl nitrate and uranium oxides with higher stoichiometric DESs urea/ChCl (2:1) (reline) and PTSA/ChCl (1:2), respectively . Moreover, the dissolution of other uranium matrices such as Rb 2 (U­(SO 4 ) 3 ), uranium metal powder, U 3 Si 2 , (U, Pu)­O 2 , and PuO 2 has not been explored in their studies. , Previous literature reports , imply that the urea (reline) and para-toluene sulphonic acid (PTSA) act as monodentate ligands via the oxygen atom. Hence, it was anticipated that these ligands are unable to offer very strong interactions for the U metal ion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parameters are given DES at 2D nanomaterial interfaces [ 313 ] 78 ChCl:Urea (1:2) No name of FF. Parameters are given DES with different nanotubes [ 324 ] 79 ChCl:Urea (1:2) Combine force field based on CGenFF and CHARMM 36 DES nanodroplet at carbon material [ 323 ] 80 ChCl:Urea (1:2) GAFF/ charges scaling is 0.9 for the ions DES droplets on ionic substrates [ 320 ] 81 ChCl:Urea (1:2) OPLS-AA/no corrections Dissolution of cellulose in DES [ 21 ] 82 ChCl:Urea (1:2) q4-MD force field/no corrections Molecular encapsulation [ 386 ] 83 ChCl:Urea (1:2) Monte Carlo/Empirical potential structure refinement (EPSR) Investigation of DES structure [ 387 ] 84 ChCl:Urea (1:2) OPLS-AA/no corrections Separation of uranyl Ions [ 388 ...…”
Section: Table A1mentioning
confidence: 99%
“…The study of Gupta et al ( [60]) investigated the behavior of uranyl ions (UO2 2+ ) dissolved in a DES made of ChCl and urea. The interaction between uranium and the DES was found to modify its redox behavior, which was studied by electrochemical techniques such as voltammetry.…”
Section: Dess For the Electrochemical Recovery Of Metalsmentioning
confidence: 99%